1995
DOI: 10.1111/j.1440-1827.1995.tb03432.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary malignant lymphoma of the intestine: Clinicopathologic and immunohistochemical studies of 39 cases

Abstract: Clinicopathologic and immunohistochemical features in 39 cases of primary intestinal non-Hodgkin's lymphoma (NHL) in Japanese patients were studied. Only resection materials in state IE and IIE-1 were included in this study because of the certainty that the intestine was the primary site of the lymphoma. The updated Kiel classification was used to classify NHL. Histologically, only two cases (5.1%) were follicular lymphomas, and the others were diffuse lymphomas. Twenty-eight patients (71.8%) had high-grade NH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…Although, according to the literature, most primary intestinal B-cell lymphomas are of MALT type, 34,35 we failed to detect MALT features, such as reactive B-cell follicles, centrocyte-like cells, and lymphoepithelial lesions, in 18 large B-cell lymphomas. When we compared large cell MALT lymphomas with large cell lymphomas that did not have a MALT component, the PIs were about the same, but the AIs in the large cell MALT lymphomas were lower (although the difference was not significant).…”
Section: Discussioncontrasting
confidence: 57%
“…Although, according to the literature, most primary intestinal B-cell lymphomas are of MALT type, 34,35 we failed to detect MALT features, such as reactive B-cell follicles, centrocyte-like cells, and lymphoepithelial lesions, in 18 large B-cell lymphomas. When we compared large cell MALT lymphomas with large cell lymphomas that did not have a MALT component, the PIs were about the same, but the AIs in the large cell MALT lymphomas were lower (although the difference was not significant).…”
Section: Discussioncontrasting
confidence: 57%
“…Other investigators studied fewer cases with or without gastric/colorectal lesions based only on univariate analyses. These investigators found that stage, 6,23 radical resection, 6 gender, 23 histologic grade, 27,29 and T-cell/B-cell phenotype 28 appeared to be correlated with survival probability. The majority of such previously reported factors were concordant with our results based on a univariate analysis ( Table 4).…”
Section: Discussionmentioning
confidence: 96%
“…To our knowledge the majority of published series have been small, and also have been combined with gastric and/or colorectal lymphomas. [22][23][24][25][26][27][28][29] To our knowledge, the current study of 80 cases with primary lymphoma of the small intestine is the third largest series reported. 5,15 In this study, we …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, low‐grade MALT lymphomas arising in the intestine usually presented with polypoid lesions and showed no association with H. pylori infection. 14–17 However, the relationship between gastric and intestinal MALT lymphomas remains to be elucidated.…”
mentioning
confidence: 99%